51.6k views
4 votes
Please help meeee!!!!!! complete the equation below. (4x)^-2(4x)^3(4x)^9 =(4x)______.

User Aanrv
by
4.6k points

2 Answers

5 votes

please help meeee!!!!!! complete the equation below. (4x)^-2(4x)^3(4x)^9 =(4x)=10

User EvgK
by
4.8k points
4 votes

Answer for the blank is: 10

The exponents are -2, 3 and 9. Note how the bases are all the same at 4x. When we multiply exponential expressions like this, we add the exponents. So we'll get -2+3+9 = 1+9 = 10 as the final exponent over the base 4x

In short,


(4x)^(-2)*(4x)^3*(4x)^9 =(4x)^(-2+3+9) = (4x)^(10)

User Yusuf Kandemir
by
4.9k points